(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2024)
The inventory, enshrined in Article 216 of the 1988 Federal Constitution, is one of the oldest mechanisms for safeguarding Brazil’s cultural heritage, and stands out for its importance in identifying and contextualizing the different tangible and intangible cultural assets. Although it lacks specific infra-constitutional regulations, the inventory plays an important role in imposing restrictive effects on property rights, which can lead to a lack of coordination in the process of understanding cultural property and its integration into communities. In Minas Gerais, Bill 1.698/2007 sought to regulate the inventory, facing challenges in defining its purposes and the resulting legal effects, mainly by distinguishing it from tombamento. This article is based on a qualitative methodological approach, with a descriptive analysis based on a reading of the heritage charters and bibliographical research on the history of the use of the inventory at IPHAN. Documentary research was carried out in the archival collection of IEPHA/MG on the implementation of the Inventory for the Protection of the Cultural Heritage of Minas Gerais - IPAC/MG. On the website of the Legislative Assembly of Minas Gerais, research was carried out into the bills being processed to regulate the protection instrument and, finally, on the website of the Court of Justice of Minas Gerais, a search was carried out for judgments on inventoried assets in order to analyze case law. In this study, we sought a synthesis of analysis that unfolds in the understanding of the inventory as an instrument of knowledge and management, which has a declaratory and precautionary character, indicating the interest of preservation and imposing restrictions that protect cultural assets until the adoption of definitive measures, according to the observed jurisprudential trend. It can be concluded that legislative initiatives to regulate the inventory must respect all the presuppositions of the Democratic State of Law.